Pengaruh Gaya Kepemimpinan Kiai Terhadap Peningkatan Motivasi Belajar dan Pemahaman Ilmu Nahwu Santri - Prayogi, Muhammad; Ashari, M. Yahya (Islamic Education Management Study Program of STIT al Urwatul Wutsqo Jombang, East Java, Indonesia, 2024)
Kiai leadership is the center of change and control for the learning conditions in the boarding school. Good leadership from a good leadership of a kiai is able to realize a good quality of education for students. The purpose of this study is to detect how the influence of the kiai's leadership style on the increase in learning motivation and understanding of kiai's leadership style on increasing the motivation to learn and understanding of nahwu knowledge of santri. This research is expected to be able to provide input for the management of the boarding school in order to can develop ways of leading that have an impact on improving the quality of education. quality of education. This type of research is quantitative, using observation and questionnaire data collection methods. questionnaire. The results of the study stated that the kiai's leadership style led to students by fostering discipline, providing motivation and giving awards it leads to the type of democratic leadership style. It leads to the type of democratic leadership style. Furthermore, it was found that the kiai's leadership style had an effect on the students' learning motivation by 0.424 with a positive sign. While the effect on students' understanding of nahwu is 0.813 with a positive sign. This means that the influence of the kiai's leadership style on these two variables can have an impact towards improvement